PERSONALITY -CENTERED APPROACH IN FOREIGN LANGUAGE TEACHING AT UNIVERSITY - Pasichnyk, M.; Tupchenko, V. (Problems of Engineer-Pedagogical Education, 2023)
The article analyzes the concept of "personality-centered approach" in the process of teaching a foreign language at higher education institutions; considers the role of foreign language education in the context of higher vocational education; emphasizes the relevance of the personality-centered approach to teaching a foreign language for specific purposes. The main characteristics of the personality-centered approach are highlighted. In the framework of the work, the authors consider the content of the abovementioned approach: teaching activities and the role of students' independent work. The article emphasizes the possibilities, advantages and difficulties, and considers some variants of solving the problematic issues of applying the personality-centered approach in foreign language classes at university. The paper defines the principles characteristic of the personality-centered approach in the process of teaching a foreign language at university: self-actualization, individuality, choice, success and creativity. It is proposed to create the necessary conditions for the successful implementation of the personalitycentered approach in teaching a foreign language for specific purposes. The article emphasizes that the application of the personality-centered approach in the process of learning a foreign language at university requires efforts from both the teacher and the student. This approach stimulates students to develop their personality, search for ways of self-determination, teaches them to acquire knowledge independently, and develops the need for constant updating and enrichment of foreign language knowledge acquired at a higher education institution. In conclusion, the authors point out that, if the psychological and pedagogical conditions are met (pedagogical stimulation of students' work in order to increase motivation for selfstudy, self-analysis and self-regulation skills development; using technologies to support students' activities in performing a specific task; providing program and methodological content aimed at developing foreign language professional competence of future specialists), the effectiveness of using student-centered foreign language teaching technologies is considerably increased, benefiting the quality of foreign language teaching in the context of higher vocational education.